2018
DOI: 10.1016/j.scitotenv.2017.10.252
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence and source identification of bisphenol compounds in wastewaters

Abstract: This study reports the occurrence of eight bisphenols (BPs): bisphenol AF (BPAF), bisphenol AP (BPAP), bisphenol B (BPB), bisphenol C (BPC), bisphenol E (BPE), bisphenol F (BPF), bisphenol S (BPS) and bisphenol Z (BPZ) in wastewaters (WWs). Sample preparation involved pre-concentration with SPE cartridges (Oasis HLB), followed by derivatization using N-(tert-butyldimethylsilyl)-N-methyltrifluoroacetamide with 1% tert-butyldimethylchlorosilane. Chemical analysis was based on gas chromatography-mass spectrometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(37 citation statements)
references
References 19 publications
4
30
1
Order By: Relevance
“…In the study performed in Ljubljana (Česen et al 2018 ), from the eight tested BPs (without BPA measurement), the only one found in treated WW was BPS (40 ng/L), similar to our work. In the review from 2018, it was presented that BPA and BPS are the BPs with the highest concentrations worldwide, while the other ones (BPAF, BPAP, BPB, BPP, BPF, BPZ) are sporadic (Noszczyńska and Piotrowska-Seget 2018 ).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In the study performed in Ljubljana (Česen et al 2018 ), from the eight tested BPs (without BPA measurement), the only one found in treated WW was BPS (40 ng/L), similar to our work. In the review from 2018, it was presented that BPA and BPS are the BPs with the highest concentrations worldwide, while the other ones (BPAF, BPAP, BPB, BPP, BPF, BPZ) are sporadic (Noszczyńska and Piotrowska-Seget 2018 ).…”
Section: Resultssupporting
confidence: 90%
“…The main route of BPs into the environment is wastewater (WW), both residential and industrial. The detection frequency and concentration level are generally known for BPA (up to 84,000 ng/L in raw WW) (Gercken et al 2018 ; Wang et al 2019 ), while for BPA-like compounds, only a few reports have been presented, which found concentrations were much lower (dozens to hundreds ng/L) (Sun et al 2017 ; Česen et al 2018 ; Wang et al 2019 ; Xue and Kannan 2019 ). This limitation can be caused by problems in application of one technique for the problematic analysis of several BPs in one run.…”
Section: Introductionmentioning
confidence: 99%
“…BPAF has been detected in wastewater from water treatment plants and was also shown to be resistant to biodegradation (Sun et al, 2017). BPC is used in the preparation of flame-resistant polycarbonates, and it has also been detected in wastewater (Cesen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One of BPA the derivatives, BPC, was first reported in a patent in 1964 [ 65 ] and a brief paper regarding BPC was published in 1968 [ 66 ] as a monomer for polycarbonates, and the physical properties of the BPC homopolymer have been summarized focusing on its highly flame-resistant properties [ 4 , 67 , 68 , 69 , 70 , 71 ]. Recent research indicated that BPC is definitely released into the environment, for example, as wastewater in lakes, and is also found non-human milk samples [ 72 , 73 , 74 ]. BPC has been reported to possess the ability to influence the transcriptional activity of ERα and ERβ [ 75 , 76 ]; some computer simulation studies were applied to afford the structural basis of these biochemical observations [ 77 , 78 ].…”
Section: Dichlorodiphenyltrichloroethane (Ddt) Metabolites and Thementioning
confidence: 99%